Constance Jocelyn Ffoulkes and the Modernization of Scientific Connoisseurship. (3rd April 2017) - Ventrella, Francesco
Abstract : Constance Jocelyn Ffoulkes (1858–1950), a disciple of Giovanni Morelli (1816–91), participated in the critical exchanges that modernized European art history at the turn of the twentieth century. In producing the first comprehensive study of Italian painter Vincenzo Foppa (ca. 1427–1515), Ffoulkes also underwrote important methodological innovations in the practice of connoisseurship, notably the development of a philological method that blended documentary evidence with direct visual examination. This article investigates Ffoulkes' interest in the use and function of photographic reproductions of archival documents and her allegiance to the "historical standpoint" championed by professional journals such as Repertorium für Kunstwissenschaft and Rassegna d'arte, to which she contributed. Emphasizing the boundaries that Ffoulkes was obliged to negotiate to secure a foothold within the male profession of art history, this article tracks the evolution of her research methods relative to the international network that enabled and recognized her expertise in the connoisseurship of Italian art.